The Development of the Indonesian Language in Egypt and Its Impact on Bilateral Relations between Indonesia and Egypt - Masukiplee Kuru; Winda Dewi Pusvita (UIN Raden Mas Said Surakarta, Indonesia, 2024)
The interest in learning the Indonesian language is inseparable from the historical, cultural, and educational relations between Indonesia and Egypt. Increased cooperation in the field of education and diplomacy between the two countries has also encouraged the spread of the Indonesian language in Egypt. This article explores the development of the Indonesian language in Egypt in 2024, including the factors influencing its spread, the challenges faced, and the impact of learning Indonesian among the Egyptian people. The Indonesian language has experienced a significant increase in interest and use among the Egyptian people, both in the fields of education and culture. This study uses a qualitative approach with interview, observation, and literature analysis methods from various relevant international journals to collect data. The results of the study show that factors such as cultural diplomacy, educational cooperation, and the role of the Indonesian diaspora in Egypt are the main drivers in the development of the Indonesian language in the country. In addition, the results of the study show that Indonesian is increasingly in demand in Egypt, especially among academics and students who are interested in studying Indonesia and bilateral relations between the two countries.